Comparative efficacy of exercise modalities for cardiopulmonary function in hemodialysis patients: A systematic review and network meta-analysis - Zang, Wanli; Fang, Mingqing; He, He; Mu, Liang; Zheng, Xiaoqin; Shu, Heng; Ge, Nan; Wang, Su (Frontiers in Public Health, 2022)
Background: To provide reliable evidence to exercise rehabilitation therapists and clinicians, we compared and analyzed the effects of different exercise modalities on cardiopulmonary function in hemodialysis patients by Bayesian network meta-analysis. Methods: We searched PubMed, OVID, Web of Science, Cochrane Library, Embase, Scopus, CINAHL, SPORT Discus, SinoMed, CNKI, Wanfang, VIP. The search time limit was from the establishment of the database to July 20, 2022. We included randomized controlled trials comparing 12 exercise modalities to intervene in cardiorespiratory fitness in hemodialysis patients. We use R software and Stata for statistical analysis. Result: A total of 82 randomized controlled trials comprising 4146 maintenance hemodialysis patients were included in this study. A direct meta-analysis showed that all exercise modalities had a positive effect on all indicators of cardiorespiratory fitness, except for the intervention of electrical muscle stimulation, which increased arterial blood pressure. Direct meta-analysis showed that BFRT, CE, IMT, CT, and AT were significantly better than controls for 6-minute walkability, MICT, CT, CE, AT, were considerably better than controls for VO2Peak, MBT and CT were significantly better than controls for SBP, and only MBT was significantly better than controls for DBP. The two-dimensional and radar plots showed that combined aerobic and resistance training had the best-combined effect on each index of cardiorespiratory fitness. Subgroup and sensitivity analyses showed stable results. The evidence for this network meta-analysis was mainly "low" to "very low". Conclusion: There is no one exercise mode that can achieve the best effect on each index. Reducing arterial blood pressure by MBT is incomparable with other exercise methods. The intervention effect of the Combination of aerobic and resistance is better and more stable. MEST can be used in patients who do not want to exercise actively but may cause an increase in blood pressure. Guideline makers, physicians, and patients can use them accurately according to the characteristics of different exercise styles.